2010
DOI: 10.1063/1.3310024
|View full text |Cite
|
Sign up to set email alerts
|

High current diffuse dielectric barrier discharge in atmospheric pressure air for the deposition of thin silica-like films

Abstract: The diffuse dielectric barrier discharge in atmospheric pressure air was applied for the thin film deposition on polymeric web in industrially relevant roll-to-roll configuration. The silica-like film deposition was performed using the admixture of hexamethyldisiloxane precursor to air flow. Fast discharge imaging at 2 μs exposure time confirms plasma uniformity in a single current pulse time scale. Morphology and composition analyses indicate that the process results in ultrasmooth films (roughness comparable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 18 publications
2
60
0
Order By: Relevance
“…[23] However, we have already shown that smooth inorganic silica-like as well as organic carbon-rich films can be deposited in a diffuse glow-like discharge operating in cost-efficient nitrogen-based gas mixtures, or, even, using air as the process gas. [25] A number of process parameters has a significant effect on the general properties of the PECVD synthesized barrier film such as chemical composition, morphology, film density and adhesion to the substrate. Some of these correlations were already discussed in selected publications from our group.…”
Section: Introductionmentioning
confidence: 99%
“…[23] However, we have already shown that smooth inorganic silica-like as well as organic carbon-rich films can be deposited in a diffuse glow-like discharge operating in cost-efficient nitrogen-based gas mixtures, or, even, using air as the process gas. [25] A number of process parameters has a significant effect on the general properties of the PECVD synthesized barrier film such as chemical composition, morphology, film density and adhesion to the substrate. Some of these correlations were already discussed in selected publications from our group.…”
Section: Introductionmentioning
confidence: 99%
“…According to the fast imaging analysis, during the single current pulse, this transient discharge evolved from a 'Townsend-like' mode to a 'glow-like' mode for each half cycle of the electric field [11,12]. It was also demonstrated that application of such a diffuse discharge as a plasma source for the roll-to-roll AP-PECVD process in conjunction with organosilicon precursors results in high quality inorganic silica-like thin films, which can be deposited on thermally sensitive polymeric substrates [14][15][16]. In this process, the increased discharge power density allows the synthesis of silica-like films with improved microstructure, lower impurities level and excellent gas diffusion barrier properties [16,17].…”
mentioning
confidence: 96%
“…The properties of an atmospheric-pressure high-current diffuse DBD operating at 200 kHz frequency in low cost N 2 /O 2 / Ar gas mixtures were investigated in [11][12][13][14]. According to the fast imaging analysis, during the single current pulse, this transient discharge evolved from a 'Townsend-like' mode to a 'glow-like' mode for each half cycle of the electric field [11,12].…”
mentioning
confidence: 99%
“…7 The uniformity of the plasma and the high power density make this technology of high applied value in surface treatment as well as in thin film deposition, and excellent SiO 2 -like barrier layers on polymeric substrates have been achieved. 3,8,9 Distinct regimes of plasma-polymer interactions along the electrodes were identified with AFM and SEM, and it was concluded that during the film growth process a competition between deposition and etching exists. 10 It is well known that the deposition, or the polymerization process, is very complex as numerous intermediates such as ions and radicals are generated, which can interact with the polymer surface.…”
Section: Introductionmentioning
confidence: 99%